2021
DOI: 10.1093/jhps/hnab067
|View full text |Cite
|
Sign up to set email alerts
|

The crescent sign—a predictor of hip instability in magnetic resonance arthrography

Abstract: Currently, much is debated on the optimal treatment of borderline hips, being in the continuum between stable and unstable hips. The diagnosis of stability is often difficult but is a prerequisite for further treatment. Analysis includes a variety of radiographic parameters. We observed that unstable hips often had a crescent-like gadolinium collection in the postero-inferior joint space. We therefore questioned if the ‘crescent sign’ could be an indicator for hip instability? A retrospective comparative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…The cliff sign on radiographs is said to be highly specific for hip micro-instability, up to 100% sensitive and specific in women under 32 years [ 325 ]. One study suggested utilizing dMRA to visualize a crescent shaped pooling of contrast in the posteroinferior joint space, and the crescent sign has recently been proposed as being relatively specific for the diagnosis of hip instability [ 243 ]. Another study of dMRA found a thinner anterior capsule (2.5 mm) and wider anterior recess (5.8 mm) in patients with capsular laxity at arthroscopy [ 326 ].…”
Section: Hipmentioning
confidence: 99%
“…The cliff sign on radiographs is said to be highly specific for hip micro-instability, up to 100% sensitive and specific in women under 32 years [ 325 ]. One study suggested utilizing dMRA to visualize a crescent shaped pooling of contrast in the posteroinferior joint space, and the crescent sign has recently been proposed as being relatively specific for the diagnosis of hip instability [ 243 ]. Another study of dMRA found a thinner anterior capsule (2.5 mm) and wider anterior recess (5.8 mm) in patients with capsular laxity at arthroscopy [ 326 ].…”
Section: Hipmentioning
confidence: 99%
“…3c). Letzteres wurde in der MR-Arthrographie beschrieben und ist gemäß aktueller Literatur ein nützliches Zeichen zur Beurteilung der Instabilität bei Patienten mit grenzwertiger Hüftdysplasie [84].…”
Section: Messmethoden Der Femoralen Antetorsion Besteht Die Gefahr Vo...unclassified
“…Radio stereometric analysis (RSA) has also been applied to measure the in vivo 3D kinematics of the joint by tracking the position of implanted titanium beads. However, this invasive technique limits the subject population to patients who have undergone surgical intervention and is difficult to be applied to the native hip joint (10)(11)(12)(13)(14)(15). Some hip indicators based on anteroposterior pelvic radiographs, such as reduced LCEA, subluxated femoral head, deficient acetabular wall with concomitant insufficient femoral coverage, positive femoro-epiphyseal acetabular roof (FEAR) index, upsloping lateral sourcil, can also indicate hip instability.…”
Section: Introductionmentioning
confidence: 99%